Indochina - Wargnier, Regis, 1948- (Sav, 1993)
This story is set in 1930, at the time when French colonial rule in Indochina is ending. An unmarried French woman who works in the rubber fields, raises a Vietnamese princess as if she was her own daughter. She, and her daughter both fall in love with a young French army officer, which will change both their lives significantly.